Mr. Magoo - Volume I - Hubley, John; Burness, Pete; MacDonald, Tom (Columbia Pictures, 1980)
Barefaced Flatfoot (1951): Magoo's nephew, Waldo, crashes his uncle's car into a pole. He needs $100 to fix the damage. Magoo, suspicious of Waldo's need for $100 and engrossed in detective novels, decides to follow him. As usual, Magoo is totally off, mistaking Waldo's participation in a Q&A game show for a police lineup/interrogation and "rescuing" him right out of the cash prize, accidentally clubbing him over the head, and later pushing him down an elevator shaft after mistaking him for a "sloe-eyed temptress." Everything turns out OK in the end as Magoo, jubilant after what he perceives as cracking the case, caves in and gives Waldo the money to fix the car. [www.bcdb.com]